24 MARA sponsored IKM teaching staff graduate - Shalfarina, Shahriman (2022)
KUANTAN, 19 March 2022 - Four years of commuting from Melaka to Universiti Malaysia Pahang (UMP) Pekan on a journey of almost 482 kilometres each week is not an easy matter.